2022
DOI: 10.3389/fnume.2022.892147
|View full text |Cite
|
Sign up to set email alerts
|

DOTA Conjugate of Bisphosphonate and PSMA-Inhibitor: A Promising Combination for Therapy of Prostate Cancer Related Bone Metastases

Abstract: Prostate cancer (PCa) is one of the most common cancer types worldwide. 90% of men with late stage PCa will develop bone metastases. Since the expression level of PSMA (prostate-specific membrane antigen) in bone metastases can vary significantly, a compound is being searched for which accumulates in bone metastases independently of PSMA level. With DOTA-L-Lys(SA.Pam)-PSMA-617, we present a compound that, in addition to a PSMA inhibitor as a target vector, also contains a bisphosphonate that is established as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…36 Additionally, Grus et al reported a PSMA derivative containing an additional bisphosphonate group, [ 177 Lu]Lu-DOTA-L-Lys(SA.Pam)-PSMA-617. 30 This ligand is based on PSMA-617 and pamidronate-squaric acid. It was successfully tested in mice as a hetero-bivalent therapy agent targeting both PSMA and bone metastasis for prostate cancer.…”
Section: ■ Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…36 Additionally, Grus et al reported a PSMA derivative containing an additional bisphosphonate group, [ 177 Lu]Lu-DOTA-L-Lys(SA.Pam)-PSMA-617. 30 This ligand is based on PSMA-617 and pamidronate-squaric acid. It was successfully tested in mice as a hetero-bivalent therapy agent targeting both PSMA and bone metastasis for prostate cancer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Especially, [ 68 Ga]Ga-P15-041 (Figure 2) showed high and selective accumulation in bone lesions, indicating that it is an excellent bone imaging agent for cancer patients. 25,26 To develop radionuclide therapeutic agents, Lu-177 bisphosphonates and several other related analogues, [ 177 Lu]Lu-EDTMP, 27 [ 177 Lu]Lu-ibandronate (IBA), 28 [ 177 Lu]Lu-DOTA-zoledronate, 29 [ 177 Lu]Lu-DOTA-L-Lys(SA.Pam)-PSMA-617, 30 metastasis have been introduced for clinical studies, suggesting that this is a viable treatment strategy. 31,32 Examples reported in the literature suggest that dual targeting could be useful to improve targeted radionuclide therapy.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations